2022
DOI: 10.1177/03631990221077008
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Divorce Trends and Risks: The Case of Norway 1886–2018

Abstract: Divorces have become common, but reliable longer-run historical data with several years of follow-up are scarce. This study investigates divorce trends and divorce risk based on prospective data for all Norwegian different-sex marriages formed from 1886–2018, with yearly follow-up continuing until 60 years after the wedding (N = 2.7 million). First marriages and remarriages are investigated separately, as are marriages in rural and urban areas. The results indicate a general decline in divorce risk, but not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Compared with first-married adults, remarried adults have positive attitudes toward divorce and are more likely to file for dissolution when experiencing marital distress [ 24 ]. However, another empirical study reported that the association between the number of marriages and marriage dissolution was questionable and suggested future research [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with first-married adults, remarried adults have positive attitudes toward divorce and are more likely to file for dissolution when experiencing marital distress [ 24 ]. However, another empirical study reported that the association between the number of marriages and marriage dissolution was questionable and suggested future research [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The variables considered as associated factors in this study were the parental marital dissolution history, marital-related characteristics of spouses (the main reason for getting married, how many times have marriage concluded), and the information (knowledge and skill) about their marital relationship. These variables were selected based on their association with marital dissolution [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…56 In contrast, a recent study from Norway assessing divorce trends in general indicated that marriage age has a relatively modest effect on divorce risk, particularly 10 years or more into the marriage. 57 For same-sex marriages in rural areas, an opposite trend of increasing divorce risk was observed. This may reflect a more general variability in divorce risk across different married groups.…”
Section: Discussionmentioning
confidence: 99%
“…This study is linked to a previous study on different-sex marriages and compares the same-sex marriages in the present study to the data from that study. 39 The connected study investigates differences in divorce rate among urban and rural marriages for more cohorts than those included in this study, but does not have any information for same-sex marriages. The definition of rural and urban marriages is the same in both studies (see Supplemental Material for details).…”
Section: Methods Datamentioning
confidence: 99%
“…UNDERSTANDING DIVORCE TRENDS AND RISKS: THE CASE OF NORWAY 1886–2018. Journal of Family History [3] .…”
Section: Specifications Tablementioning
confidence: 99%